2010
DOI: 10.1038/mt.2009.275
|View full text |Cite
|
Sign up to set email alerts
|

Intranodal Immunization With a Vaccinia Virus Encoding Multiple Antigenic Epitopes and Costimulatory Molecules in Metastatic Melanoma

Abstract: Recombinant vaccinia virus (rVV) encoding tumor-associated antigens (TAAs) and adhesion or costimulatory molecules may represent important immunogenic reagents for cancer immunotherapy. Recently, intranodal (IN) antigen administration was suggested to be more immunogenic than intradermal (ID) vaccination. However, IN rVV administration has not been attempted so far. We used a rVV encoding gp100(280-288), Melan-A/MART-1(27-35) and tyrosinase(1-9) HLA-A0201 restricted epitopes and CD80 and CD86 costimulatory mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Finally, it is also possible to improve the efficacy of both exogenous and endogenous DC-based vaccines by transducing DC either ex vivo or in vivo with viral vectors that encode immunostimulatory molecules. A number of studies have reported improved anti-tumor immunity when this approach was used to drive expression of CD80/CD86 costimulatory molecules (165, 166) or IL-12 (167) by DC. Collectively, these strategies highlight the advances made in tumor immunotherapy as our understanding of tumor immune suppression and evasion has evolved over the last several years.…”
Section: Immunotherapeutic Strategies For Interfering With Tumor-assomentioning
confidence: 99%
“…Finally, it is also possible to improve the efficacy of both exogenous and endogenous DC-based vaccines by transducing DC either ex vivo or in vivo with viral vectors that encode immunostimulatory molecules. A number of studies have reported improved anti-tumor immunity when this approach was used to drive expression of CD80/CD86 costimulatory molecules (165, 166) or IL-12 (167) by DC. Collectively, these strategies highlight the advances made in tumor immunotherapy as our understanding of tumor immune suppression and evasion has evolved over the last several years.…”
Section: Immunotherapeutic Strategies For Interfering With Tumor-assomentioning
confidence: 99%
“…However, these responses translated poorly into survival benefit [20]. This agent was subsequently assessed after direct injection into the inguinal lymph nodes and, again, induction of epitopespecific CTL responses was observed, but these did not correlate with improved survival [21].…”
Section: Recombinant Viral Vaccines Expressing Taasmentioning
confidence: 99%
“…Intranodal injections of vaccines based on viral vectors have been studied in melanoma patients, who responded with strong cytotoxic and other immunological T-cell responses as well as some clinical benefi ts (Adamina et al 2010 ;Spaner et al 2006 ).…”
Section: Intralymphatic Vaccination: As Good As It Getsmentioning
confidence: 99%